Correlations between biometrical characters in vanilla (Vanilla planifolia Andrews) - MADHUSOODANAN, P G SANKARAN, K M KURUVILLA, K J (Journal of Spices and Aromatic Crops, 1994)
A study was undertaken to fmd out the extent of association among growth attributes of vanilla (Vanilla planifolia) and to develop a model for determination of vine length based on biometrical observations. The characters, number of nodes, number of leaves and internodal length were significantly and positively correlated with vine length. The multiple regression equation derived exhibited a precision of 82.5 per cent.